(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe nurses’ perspectives about workplace violence. Methods: A cross-sectional study was conducted on 201 nurses who were attending training courses at Thai Nguyen Medical of Medicine and Pharmacy. Data was collected by self-administered questionnaires from March to June 2021. Results: 15.9% of respondents agreed that healthcare workers should accept violence as the nature of the works. 76.0% of nurses also believed that they were not well equipped with knowledge and skills to deal with workplace violence. The percentage of nurses who agreed that violence occurred as the consequences of insufficient professional competencies, and ineffective communication were 10.4% and 65.7%. Notably, 69.7% of respondents assumed that the current policies were not strong enough to protect them from workplace violence. Conclusions: There are needs for measures to change nurses’ attitude, knowledge and skills to deal with workplace conflict. Hospitals should improve their policies and procedures to manage violence at their institutions.